2021
DOI: 10.1002/hpm.3157
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care and skilled birth in the fragile and conflict‐affected situation of Burundi

Abstract: Burundi is a fragile and conflict‐affected state characterized by persistent conflict and political violence. Amid this conflict, Burundi has one of the highest maternal mortality rates globally—548 per 100,000 births as of 2017, such deaths could be prevented with antenatal care (ANC). This cross‐sectional study aimed to examine the association between conflict and ANC and skilled birth attendant (SBA) utilization. Logistic regression analysis was conducted using the 2016–2017 Burundi Demographic and Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Other published studies in DRC, Nigeria, and Burundi have found similar evidence, wherein fragile areas not directly affected by conflict may have maternal health indicators that are similar to or worse than those in conflict-affected areas in the same country. Their authors concluded that this phenomenon was likely due to minimal international support and investments in fragile areas [4,47,[61][62][63][64][65] compared with the settings experiencing acute conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies in DRC, Nigeria, and Burundi have found similar evidence, wherein fragile areas not directly affected by conflict may have maternal health indicators that are similar to or worse than those in conflict-affected areas in the same country. Their authors concluded that this phenomenon was likely due to minimal international support and investments in fragile areas [4,47,[61][62][63][64][65] compared with the settings experiencing acute conflict.…”
Section: Discussionmentioning
confidence: 99%